2012
DOI: 10.1186/1741-7015-10-104
|View full text |Cite
|
Sign up to set email alerts
|

New treatments for influenza

Abstract: Influenza has a long history of causing morbidity and mortality in the human population through routine seasonal spread and global pandemics. The high mutation rate of the RNA genome of the influenza virus, combined with assortment of its multiple genomic segments, promote antigenic diversity and new subtypes, allowing the virus to evade vaccines and become resistant to antiviral drugs. There is thus a continuing need for new anti-influenza therapy using novel targets and creative strategies. In this review, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 136 publications
(150 reference statements)
0
73
0
1
Order By: Relevance
“…Evidences also abound that evolving pandemic strains outsmart the annually predicted vaccine that depends solely on informed and educated guesses from the prevailing isolates and circulating strains, thus necessitating a new antiviral bullet (5,29). The effectiveness of current approaches to treatment and prevention of influenza have also been limited by factors such as the prevalence of the adamantane-resistant influenza viruses, the prohibitive cost of available drugs especially in resource-poor countries, the unpredictability of vaccine availability, and the time lag between vaccine development (25,48).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidences also abound that evolving pandemic strains outsmart the annually predicted vaccine that depends solely on informed and educated guesses from the prevailing isolates and circulating strains, thus necessitating a new antiviral bullet (5,29). The effectiveness of current approaches to treatment and prevention of influenza have also been limited by factors such as the prevalence of the adamantane-resistant influenza viruses, the prohibitive cost of available drugs especially in resource-poor countries, the unpredictability of vaccine availability, and the time lag between vaccine development (25,48).…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of current approaches to treatment and prevention of influenza have also been limited by factors such as the prevalence of the adamantane-resistant influenza viruses, the prohibitive cost of available drugs especially in resource-poor countries, the unpredictability of vaccine availability, and the time lag between vaccine development (25,48). Thus, a recent paradigm shift includes the search and quest for antiviral, redox regulator and/or anti-inflammatory strategies that could either solely emerge as new antiinfluenza or adjunct therapy combined with the existing arsenal to reduce the severity and complications of influenza infections (1,5,14,18,(45)(46)(47)(48). Data from a number of studies suggest that the use of oxygen free radicals as targets may provide an approach to the amelioration of the pathogenicity caused by influenza virus infections (15,47), and several studies have reported the anti-influenza activity of medicinally potent and disease-preventing plant polyphenols and flavonoids with antioxidant properties (9,17,24,42,47,48).…”
Section: Introductionmentioning
confidence: 99%
“…However, their low tolerance for anti-influenza drugs puts a limit on their use of these drugs. 43 This could become a serious problem if not adequately managed.…”
Section: High-risk Human Populationsmentioning
confidence: 99%
“…87 Moreover, because the design algorithms for siRNA-based agents are nearly identical for any pathogen, synthetic and mass production processes for all siRNAs are the same, and their efficiency of production is better. 43 …”
Section: Ease Of Synthesis and Better Efficiency Of Productionmentioning
confidence: 99%
See 1 more Smart Citation